An Introduction to fluid dynamics : - Middleman, Stanley (John Wiley and Sons, 1998)
This textbook provides more than sufficient material to support a one-semester course in fluid dynamics; for curricula that present fluid dynamics in a single quarter, there is an abundance of teaching material.